1999
DOI: 10.1021/np990140q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 11,12-Epoxydrim-8,12-en-11-ol, 11,12-Diacetoxydrimane, and Warburganal from (−)-Sclareol

Abstract: The first syntheses are reported for recently isolated drimanes 11,12-epoxydrim-8,12-en-11-ol (2) and 11,12-diacetoxydrimane (3), from (-)-sclareol (1). Furthermore, two efficient new routes to the potent bioactive warburganal (4) starting also from 1 are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…[19] Oxidation of (+ +)-20 with SeO 2 ,followed by hydrolysis and IBX oxidation provided the dienone aldehyde (À)-21.T he zinc-mediated Barbier-type reaction of (À)-21 and (À)-10 afforded am ixture of two separable diastereomers, (+ +)-22 a and (À)-22 b (22 a/22 b = 1.7:1) in 74 %c ombined yield. Therefore,w ep repared the sesquiterpene (+ +)-20 with 57 %overall yield in eight steps from (+ +)-sclareolide (11)byfollowing the established procedures.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[19] Oxidation of (+ +)-20 with SeO 2 ,followed by hydrolysis and IBX oxidation provided the dienone aldehyde (À)-21.T he zinc-mediated Barbier-type reaction of (À)-21 and (À)-10 afforded am ixture of two separable diastereomers, (+ +)-22 a and (À)-22 b (22 a/22 b = 1.7:1) in 74 %c ombined yield. Therefore,w ep repared the sesquiterpene (+ +)-20 with 57 %overall yield in eight steps from (+ +)-sclareolide (11)byfollowing the established procedures.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…However,t he results of mechanistic studies have complicated matters by questioning whether the anticancere ffects of vanilloids are mediated by TRPV1,a nd have revealed that TRPV1 antagonists generally do not prevent vanilloid agonist-induced cell death. [27,[29][30][31][32] Despite severalr eports of cytotoxic activity associated with polygodial, [33][34][35][36][37][38][39] to our knowledge,t his TRPV1 agonist or related bicyclic sesquiterpene dialdehydesh ave not been investigated as potential anticancer agents. This report detailso ur synthetic study of polygodial (1), the generation of as eries of polygodiala nalogues, and the evaluation of the synthesized compounds for TRPV1 and anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…, % Ratio of acetates (4)(5)(6), % Yield of hydrocarbon (12), % Driman-8α,11-diol-11monoacetate (7) 7 7 7 7 7…”
mentioning
confidence: 99%
“…), CH 3 CN, 18-20°C (c) CF 3 SO 3 SiMe 3 (1 eq. ), CH 3 Obviously it would be interesting to perform regioselective elimination of a C 8 -functional group of 7 or 8 to form only one of the possible acetates (4)(5)(6). The use of several reagents to achieve this goal has been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation